Rheology - De Vicente, Juan (IntechOpen, 2012)
This book contains a wealth of useful information on current rheology research. By covering a broad variety of rheology-related topics, this e-book is addressed to a wide spectrum of academic and applied researchers and scientists but it could also prove useful to industry specialists. The subject areas include, polymer gels, food rheology, drilling fluids and liquid crystals among others.